Transcriptome analysis of auxin transcription factor OsARF17-mediated rice stripe mosaic virus response in rice - Ma, Qiang; Wang, Fengmin; Song, Weiqi; Huang, Chaorui; Xie, Kaili; Wei, Zhongyan; Li, Yanjun; Chen, Jianping; Zhang, Hehong; Sun, Zongtao (Frontiers in Microbiology, 2023)
Plant auxin response factors (ARFs) play an irreplaceable role in regulating the expression of auxin response genes. Our previous studies have indicated that auxin response factor OsARF17 plays a crucial role in plant defense against diverse rice viruses. To further elucidate the molecular mechanism of OsARF17 in antiviral defense pathway, we performed a comparative transcriptome analysis of Rice stripe mosaic virus (RSMV)-inoculated OsARF17 mutant rice plants. KEGG enrichment analyses showed that the down-regulated differentially expressed genes (DEGs) belonged to plant-pathogen interaction and plant hormone signal transduction pathways were markedly enriched in OsARF17 mutants under RSMV inoculation. Furthermore, Gene ontology (GO) analyses revealed that these genes were enriched in a variety of hormone biosynthetic process, including jasmonic acid (JA), auxin, and abscisic acid (ABA). RT-qPCR assays showed that the induction of plant defense-related genes, such as WRKY transcription factors, OsAHT2 and OsDR8, and JA-related genes, were significantly suppressed in OsARF17 mutants in response to RSMV. Therefore, our study reveals that OsARF17-mediated antiviral immunity may be achieved through affecting the interaction between different phytohormones and regulating defense gene expression in rice. This study provides new insights into the molecular mechanisms of auxin signaling in the rice-virus interaction.